A BRIEF STUDY OF CATERING MANAGEMENT IN NVS WITH SPECIAL REFERENCE TO A SCHOOL OF JAIPUR REGION (International Journal of Food and Nutritional Sciences, 2023)
JNV is an experimental Indian school. It targets brilliant kids and tries to provide them a superior education like residential schools. Even in disadvantaged areas, these kids are omnipresent. Poor people lack access to high-quality education. Children with special talent or ability should have access to excellent education. This research examines catering management at Jaipur's JNV. The Jaipur school has severe catering rules. The Vidyalaya has boys' and girls' dining rooms. Students consume nutritious food. Vidyalaya administration and students create a menu for migrant students. Present research work includes data collection through personal interaction with the school authority and t-test and ANNOVA statistical tool has been used to analyze the data. SPSS and MS-Excel were also use while data analysis. Present research is based on the view of students which includes their view towards food as well as environment of place where they used to eat.